PREDICTION OF CO, SO2, NO2, PM2,5, AND PM10 DISPERSION FROM THE EMISSION OF THE TRANSPORTATION, INDUSTRY, RESIDENTIAL, AND POWER SECTOR IN THE CITY AND REGENCY OF BEKASI, WEST JAVA USING AERMOD SOFTWARE - Maura Bernadine, Cindy
The City and Regency of Bekasi are directly adjacent to the Special Capital Region of Jakarta and acts as a buffer zone to alleviate pressure on the population development of DKI Jakarta as the capital city. Apart from being a residential center, Bekasi City and Regency also develop in trade, services and education. This may facilitate a decrease in environmental quality, including air pollution. One way to prevent air pollution is to predict the concentration of air pollutants by modeling air pollutant dispersion. In this study, air pollutant dispersion modeling was carried out using AERMOD software for CO, SO2, NO2, PM2.5, and PM10 pollutants. The AERMOD software uses meteorological data processed through the AERMET program and area contour data processed through the AERMAP program. The study used grid with the size of 2 km x 2 km with inventory data of Bekasi City and Regency's emission load in 2017 for the transportation, industry, residential, and power sectors. From the study results, the highest concentrations for CO, SO2, NO2, PM2.5, and PM10 pollutants were 3411 µg/m³, 191 µg/m³, 1.09 µg/m³, 7.23 µg/m³, and 7.42 µg/m³, respectively. The pollutants concentration from the model are still below the ambient air quality standard based on Government Regulation No. 22 of 2021 except for NO2 with a measurement time of 24 hours and 1 year.